Hand grip strength in dentists: A comprehensive evaluation of head position, dominance, age, and sex - Mahmoud, Hayam; Shalabi, K. M.; Battecha, Kadrya H.; Abd El-Kafy, Ehab Mohamed; Alayat, Mohamed Salaheldein; Ebid, Anwar A.; Ahmad, Jana Sami; Alotaibi, Atheer Mohammed; Alsfyani, Nouf Fayez; Alzhrani, Jumana Jamaan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to identify the effect of different head positions on hand grip strength (HGS) on account of hand dominance, age, and sex in dentists. A total of 197 dental students (DS) and practitioners (DP) (81 females and 50 males were DS, 10 females and 14 males were (DP) aged 19-63 participated. HGS was measured using a dynamometer, and the head angle was determined with an inclinometer. HGS on both sides was greatest in NHP & displayed least strength in HEP. There was a significant difference in HGS measured in NHP, HFP, and HEP (p < 0.05) for the dominant hand, while the non-dominant hand showed no significant difference (p > 0.05) for female DS. A significant difference was recorded between dominant and non-dominant HGS in each head position (p < 0.05). Significant differences were also found between female and male DP HGS (p < 0.05) and DS (p < 0.05), particularly at HFP and HEP. There was a significant difference noted between female DS and DP HGS, however, HGS for both dominant and non-dominant hands in DP was higher than DS in HEP (p < 0.05), while no significant difference noted for HFP and NHP. Females had the strongest grip in NHP, while males in HFP. HGS influenced by age; DP had stronger grip than DS. In a comparison between male and female DP and DS, males had stronger grip than females across all positions. Hand dominance significantly influences HGS, with the dominant having a stronger hand grip.